Effect of free-weight resistance training on functional fitness in elderly woman - Buzzachera, Cosme Franklim; Elsangedy, Hassan Mohamed; Krinski, Kleverton; Colombo, Heriberto; de Campos, Wagner; Silva, Sergio Gregório da (Journal of Physical Education (Maringá), 2008)
The resistance training has been indicated as a strategy to reduce the organic modification with the increase of age. The aim of this study was to investigate the effects of a 12-week free-weight resistance training on the functional fitness of elderly women. Fourteen older women (mean age: 65.5±3.9 years) participated in a 12-week free-weight resistance training program (3x/week, 10 exercises, 1x10-RM, 1 min rest interval). Before and after training, upper body strength, upper and lower body muscular endurance, grip strength, cardiorrespiratory fitness, flexibility and balance/agility were measured. The results demonstrated that after 12 weeks of resistance training, upper body strength (24.2±8.2 to 29.6±2.1), upper body muscular endurance (14.6±2.8 to 20.2±2.1), grip strength (21±9.4 to 23.4±5), cardiorrespiratory fitness (542.2±47.9 to 571.2±39.6), and flexibility (1.7±8 to 4.1±7.5) increased significantly above baseline (P<0.05). There were nonsignificant improvements in the lower body muscular endurance and balance/agility. These findings indicate that 12-week free-weight resistance training can produce substantial improvements on the functional fitness of elderly women. These data do reinforce that free-weight resistance training is a safe and effective way to minimize the functional and structural declines occurred with aging.